Importance of adiponectin activity in the pathogenesis of Alzheimer's disease. Issue 8 (11th July 2017) - Waragai, Masaaki; Ho, Gilbert; Takamatsu, Yoshiki; Sekiyama, Kazunari; Sugama, Shuei; Takenouchi, Takato; Masliah, Eliezer; Hashimoto, Makoto
Abstract: A recent study suggested that insulin resistance may play a central role in the pathogenesis of Alzheimer's disease (AD). In this regard, it is of note that upregulation of plasma adiponectin (APN), a benign adipokine that sensitizes the insulin receptor signaling pathway and suppresses inflammation, has recently been associated with the severities of amyloid deposits and cognitive deficits in the elderly, suggesting that APN may enhance the risk of AD. These results are unanticipated because AD has been linked to type II diabetes and other metabolic disorders in which hypoadiponectinemia has been firmly established, and because APN ameliorated neuropathological features in a mouse model of neurodegeneration. Therefore, the objective of this study is to discuss the possible mechanisms underlying the biological actions of APN in the context of AD. Given that insulin receptor signaling is required for normal function of the nervous system, we predict that APN may be upregulated to compensate for compromised activity of the insulin receptor signaling pathway. However, increased APN might be sequestered by tau in the brain, leading to neurotoxic protein aggregation in AD. Alternatively, misfolding of APN may result in downregulation of the insulin/APN signal transduction network, leading to decreased neuroprotective and neurotrophic activities. Thus, it is possible that both 'gain of function' and 'loss of function' of APN may underlie synaptic dysfunction and neuronal cell death in AD. Such a unique biological mechanism underlying APN function in AD may require a novel therapeutic strategy that is distinct from previous treatment for metabolic disorders.